Never the Twain Shall Meet: Disorienting East and West in Teaching and Scholarship - Shields, James Mark (Bulletin for the study of religion, 2015)
This article explores the categories of "East" and "West" within teaching and scholarship on Asian religions. After reflection on both the problematic and useful aspects of these terms in classroom pedagogy, I analyze the life and work of Hirai Kinza (1859-1916), a Japanese lay Buddhist who experimented with Unitarianism and socialism in an attempt to bridge "East" and "West" in the context of Japanese modernization.